System Dynamics Modeling of Sustainable Ecotourism: A Triple Bottom Line Scenario Analysis in Wonosantri, Indonesia - Aulia Amanda Syahputri; Fitria Dina Riana; Agustina Shinta Hartati Wahyuningtyas (Jurnal Manajemen dan Agribisnis, 2026)
Background: Ecotourism is a form of natural resource utilization that is oriented towards sustainability. Therefore, its management must take into account environmental, social, and economic aspects in a balanced manner.Purpose: This study aims to identify the dynamics of ecotourism conditions in the 2030 projection and formulate the best development scenario.Design/methodology/approach: The data used in this study are primary data obtained from in-depth interviews with key informants and secondary data from internal sources, BPS data, and supporting literature. This study uses a dynamic system analysis method that includes variable identification, the creation of a Cause Loop Diagram (CLD), a Stock and Flow Diagram (SFD), and the determination of the best scenario to recommend.Finding/Result: The findings indicate that the absence of targeted interventions has caused visitor numbers and revenue to stagnate or decline. With the recommendations of the Environmental and Governance Improvement Scenario, a 162% increase in tourist numbers was recorded in the high scenario. This increase in tourist numbers was followed by an even higher increase in revenue, which reached 178.6%.Conclusion: These findings indicate that the development of dynamic system scenarios is crucial for maintaining the sustainability of ecotourism from economic, social, institutional, and environmental dimensions, with the Environmental Improvement and Governance Scenario being the most effective scenario in improving the overall performance of the ecotourism system.Originality/value (State of the art): This study provides an overview of the application of the triple bottom line concept in dynamic ecotourism system modeling. Its originality lies in its ability to model real conditions based on existing data. The findings regarding recommendations for the best management scenarios for ecotourism provide practical contributions that are applicable and can be directly implemented by managers in strategic decision-making. Keywords: ecotourism, dynamic systems, triple bottom line, governance scenario, development scenario